Mahakarya Melayu dalam abad 21 - Abdul Manaf, Nor Faridah; Hashim, Ruzy Suliza (Persatuan Penulis National Malaysia, 2006)
This article discusses criteria needed for writing great literary work.There is also a comparative study made of achievements of literary giants produced outside Malaysia and local giants - what made them great writers? There are recommendations for Malaysian writers and scholars on promoting great art.